Massive fish mortality in Ismarida Lake, Greece: identification of drivers contributing to the fish kill event - KOUTRAKIS, E.; EMFIETZIS, G.; SYLAIOS, G.; ZOIDOU, M.; KATSIAPI, M.; MOUSTAKA-GOUNI, M. (Mediterranean Marine Science, 2016)
During the end of August 2013, a massive fish mortality occurred in Ismarida Lake, a small and shallow system of Northern Greece, where approximately 10-18 tons of euryhaline fish died. This study attempts to describe the event of this fish kill or Massive Fish Mortality (MFM) that occurred in Ismarida Lake during the night of August 28, 2013, and to identify the possible drivers that may have triggered this event. A combined hydrographic, ichthyological and phytoplankton survey were carried out along with a toxicological analysis. Finally, the study proposes both short-term and long-term measures for the management of both quality and quantity of the water (ground and surface) resources in the broader basin of Ismarida Lake.